DEVELOPMENT OF DIGITAL COMIC LEARNING MEDIA IN SCIENCE SUBJECT FOR GRADE III AT SD PAB 25 MEDAN ACADEMIC YEAR 2024/2025 - Diana Syafitri; Indah Pratiwi (Journal of Innovation in Research, Education and Culture (JIREC), 2026)
This research is a Research and Development (R&D) study that produces a product in the form of digital comic media in science learning for Grade III at SD PAB 25 Medan. This study aims to determine the steps in developing digital comic media in science learning at SD PAB 25 Medan, to examine the validity of digital comic media in science learning at SD PAB 25 Medan, and to examine the practicality of digital comic media in science learning at SD PAB 25. This study uses the ADDIE model, namely Analysis, Design, Development, Implementation, Evaluation. The results of the development based on expert assessment show that the material expert validator obtained 90% “very valid”, and the media design expert obtained 98% “very valid”. The practicality from educators based on teacher responses obtained 90% “very practical”. The trial conducted in Grade III at SD PAB 25 Medan with a total of 25 students showed that the overall student response reached 86% in the “very practical” category.